Finding the nerve : the story of impedance neurography - Cory, Philip C. (Academic Press, 2017)
Finding the Nerve: The Story of Impedance Neurography discusses research that elucidates the nature of nerve simulation via externally applied electrical fields, and how it has led to an entirely new understanding of neuronal cell membrane biophysics and defined a novel nerve imaging technology. It details how these discoveries came about and the nature of research that derives from unexplained clinical observations. The primary technology, impedance neurography, is a wholly new way of nerve-specific visualization in 2-D or 3-D, with the ability to define both normal and abnormal functioning of nerves, heretofore unavailable from techniques such as MRI neurography. This is of particular importance with respect to the obesity epidemic where physicians performing nerve-related procedures cannot use ultrasound visualization due to the depth limitations of that technology.